Analysis of the Influence of Mobbing and Violence Acts on the Safety of Workers - Korkmaz, Murat; Kilic, Bulent; Yucel, Ali Serdar; Atalay, Ahmet; Akbulut, A. Kursad; Gurkan, Ayca (Kamla-Raj Enterprises, 2015)
The aim of this study is to identify the factors responsible for the safety and violence problems faced by doctors and healthcare workers at private and state institutions. This study, which is a practical research, was conducted with the subjects selected from Istanbul; Diyarbakir, Urfa, Ankara, Izmir, Bursa, Trabzon, Samsun, Tekirdao and Van within the borders of Turkey. A total of 1792 healthcare workers participated in this study. The study lasted for almost 11 months. All of the participants were chosen randomly. Following the reliability analysis, the Cronbach alpha coefficient was found to be 0.821. In this study, the hypothesis tests were applied, and reliability analysis, frequency tables, descriptive statistics, independent sample t-test and one-way variance analysis were used as part of the analysis. It has been detected in the study that the participating healthcare workers have concerns over occupational safety and legal rights and that the current laws do not protect them, and that they experience traumatic problems due to the violence perpetrated by the patients and patient relatives who do not respect their profession and professional responsibilities accordingly.
Keywords: Health; Occupation; Security; Violence; Law; Doctor; Worker; Risk; Court; Anxiety; Trauma